A "Step-Ramp-Step" protocol to identify the maximal metabolic steady state - Iannetta, D.; Calaine Inglis, E.; Pogliaghi, S.; Murias, J. M.; Keir, D. A. (Medicine & Science in Sports & Exercise, 2020)
The oxygen uptake (V.O2) at the respiratory compensation point (RCP) closely identifies with the maximal metabolic steady state. However, the power output (PO) at RCP cannot be determined from contemporary ramp-incremental exercise protocols. Purpose: This study aimed to test the efficacy of a "step-ramp-step" (SRS) cycling protocol for estimating the PO at RCP and the validity of RCP as a maximal metabolic steady-state surrogate. Methods: Ten heathy volunteers (5 women; age: 30 ± 7 yr; V?O2max: 54 ± 6 mL·kg-1·min-1) performed in the following series: a moderate step transition to 100 W (MOD), ramp (30 W·min-1), and after 30 min of recovery, step transition to ~50% POpeak (HVY). Ventilatory and gas exchange data from the ramp were used to identify the V.O2 at lactate threshold (LT) and RCP. The PO at LT was determined by the linear regression of the V.O2 versus PO relationship after adjusting ramp data by the difference between the ramp PO at the steady-state V.O2 from MOD and 100 W. Linear regression between the V?O2-PO values associated with LT and HVY provided, by extrapolation, the PO at RCP. Participants then performed 30-min constant-power tests at the SRS-estimated RCP and 5% above this PO. Results: All participants completed 30 min of constant-power exercise at the SRS-estimated RCP achieving steady-state V.O2 of 3176 ± 595 mL·min-1 that was not different (P = 0.80) from the ramp-identified RCP (3095 ± 570 mL·min-1) and highly consistent within participants (bias = -26 mL·min-1, r = 0.97, coefficient of variation = 2.3% ± 2.8%). At 5% above the SRS-estimated RCP, four participants could not complete 30 min and all, but two exhibited non-steady-state responses in blood lactate and V.O2. Conclusions: In healthy individuals cycling at their preferred cadence, the SRS protocol and the RCP are capable of accurately predicting the PO associated with maximal metabolic steady state.